Laboratory Findings, Compassionate Use of Favipiravir, and Outcome in Patients With Ebola Virus Disease, Guinea, 2015—A Retrospective Observational Study. (21st February 2019) - Kerber, Romy; Lorenz, Eva; Duraffour, Sophie; Sissoko, Daouda; Rudolf, Martin; Jaeger, Anna; Cisse, Sekou Ditinn; Camara, Alseny-Modet; Miranda, Osvaldo; Castro, Carlos M; Akoi Bore, Joseph; Raymond Koundouno, Fara; et al.
Abstract : In 2015, favipiravir was administered on a compassionate-use basis to patients with Ebola virus disease in Guinea. This study reveals a trend toward improved survival in favipiravir-treated patients; however, the effect of treatment was not statistically significant, except for its influence on survival time. Abstract: Background: In 2015, the laboratory at the Ebola treatment center in Coyah, Guinea, confirmed Ebola virus disease (EVD) in 286 patients. The cycle threshold (Ct) of an Ebola virus–specific reverse transcription–polymerase chain reaction assay and 13 blood chemistry parameters were measured on admission and during hospitalization. Favipiravir treatment was offered to patients with EVD on a compassionate-use basis. Methods: To reduce biases in the raw field data, we carefully selected 163 of 286 patients with EVD for a retrospective study to assess associations between potential risk factors, alterations in blood chemistry findings, favipiravir treatment, and outcome. Results: The case-fatality rate in favipiravir-treated patients was lower than in untreated patients (42.5% [31 of 73] vs 57.8% [52 of 90]; P = .053 by univariate analysis). In multivariate regression analysis, a higher Ct and a younger age were associated with survival ( P < .001), while favipiravir treatment showed no statistically significant effect ( P = .11). However, Kaplan-Meier analysis indicated a longer survival time in the favipiravir-treated group ( P = .015). The study also showed characteristic changes in blood chemistry findings in patients who died, compared with survivors. Conclusions: Consistent with the JIKI trial, this retrospective study revealed a trend toward improved survival in favipiravir- treated patients; however, the effect of treatment was not statistically significant, except for its influence on survival time.